A NEW DIRECTION OF MANUFACTURING PREPARATION FOR METALLURGY AND MECHANICAL BUILDING - Ogins’kyy, Josef; Vlasov, Andrii; Grydin, Olexandr; Hrechanyi, Oleksii; Vasilchenko, Tetyana (Scientific Journal "Metallurgy", 2024)
A fundamentally new method of obtaining blanks for grade rolling, pipe production and machine building has been developed. The method is based on the use of the roll castingrolling process. A fundamentally new design of the casting-rolling installation has been developed, it includes three crystallizer rolls, which, together with other equipment of the installation, form a volumetric inter-roll space, where a three-dimensional massive body of the workpiece is created, the design device is protected by a patent of Ukraine for an invention. The method and device make it possible to obtain solid and hollow blanks that can have a dual purpose. Design solutions are based on proven original analogs. The developments have undergone initial testing in the laboratory of the department of metallurgical equipment of the Zaporizhia National University. The testing was experimental in nature, the main task was to test the design of the installation and the new method. As a result of the approbation, the manufacturability of the method and device was established, the prospects of their development and application in industrial conditions were confirmed. The workability of the method of obtaining blanks and the device for its implementation has been confirmed. The industrial production of solid and hollow billets by the roll casting-rolling method will improve the technical and economic indicators of metallurgical and machine-building enterprises: shorten the metallurgical cycle, reduce energy costs, reduce the metal capacity of equipment, and improve the environmental condition. The results of the development can be used by enterprises of metallurgical, machine-building complexes, and the defense industry. The availability of new type of blanks allows to revise the composition of the equipment of rolling mills and pipe shops in the direction of reducing its volume and energy consumption. In the future, new developments become the basis for the creation of endless graded rolling.